KAJIAN PENERAPAN ZONA PENGENDALIAN LALU LINTAS PADA PELAKSANAAN PEKERJAAN JALAN - Rio Andika; Purnawan Purnawan; Elsa Eka Putri (Rang Teknik Journal, 2020)
Road works are almost close with moving traffic and potentially causing traffic disruption, congestion, delay, frustration, and more can cause collisions that would injure or kill road users and road workers. In order to remain resilient, the road worker must apply the zone concept on road works. This study aims to evaluate the application of Safety Technical Guidance on Road Work Location conducted by PT. Citra Muda Noer Bersaudara on Road Reconstruction of Junction (Koto Baru) - Jambi Border segment. So do a direct observation of the road work zone implemented by the contractor and compare it with the applicability in the guide. The implementation of the road work zone carried out by the contractor on the work package under review still lacks. In the implementation, the lack of which always occurs in every job implementation is the absence of a termination zone in all types of work, the transition zone is only applied to asphalt work, the early warning zone is only applied to road concrete work, asphalt overlay work and road shoulder work. Speed survey results show that the implementation of road work zone applied by the contractor can reduce the speed of the vehicle.